Comprehensive analysis of pan-cancer reveals the potential of SLC16A1 as a prognostic and immunological biomarker. Issue 11 (17th March 2023) - Chen, Lingyun; Li, Yang; Deng, Xinna
Abstract : SLC16A1 plays an important role in the development of multiple cancer types. Pan-cancer analysis may have significant impacts on the exploration of the relationship between SLC16A1 gene expression, prognosis and the molecular mechanisms of tumorigenesis. In this study, through the analysis of TCGA and GEO datasets, we explored the expression level and survival prognosis of SLC16A1 in pan-cancer, and further explored the differences in SLC16A1 gene mutation, methylation, and phosphorylation between tumor and normal tissues. In addition, we focused on the biological function of this gene and the relationship between the prognosis and immune infiltration by immune infiltration analysis and enrichment analysis, in order to evaluate the diagnostic and prognostic significance of SLC16A1 in carcinomas. The study found that SLC16A1 was highly expressed in 14 kinds of tumors, and there were statistically significant differences in the prognosis of 9 tumors. The phosphorylation level of S467 increased in OV, RCC, and UCEC. There was a statistically negative correlation between the CD8+ T-cell infiltration level and the SLC16A1 expression in HNSC, LUSC, SARC, TGCT, and KIRC. The cancer-related fibroblasts were positively correlated with SLC16A1 expression in BLCA, BRCA, KIRC, KIRP, PAAD, PCPG, and THCA. The enrichment analysis indicated that the tumorigenesis mechanism of this gene was mainly related to "glycolysis and glucose metabolism synthesis." SLC16A1 was a promising prognostic and immunological biomarker in pan-cancer.